Sleep and its Disorders Affect Society - Idzikowski, Chris (IntechOpen, 2014)
This book consists of a diverse set of topics which cover not only the predominant interests in sleep medicine such as sleep apnoea but also the more esoteric areas such as forensic sleep medicine. The chapters provide contemporary reviews and analysis of the existing literature. They are useful not only for the general and specialist practitioner who is trying to get up to speed or keep up with their area but also for researchers who are trying to understand these areas for the first time. Where necessary, the authors have highlighted areas that need further research and also those areas that should concern both medical and public health authorities.